Ecocide in the Light of Criminal Law with the Formation of Criminal Behaviors in Environmental Degradation - Mehrad Roozbeh; Neusha Ghahremani Afshar; Abbasali Akbari; Mohammad Taghi Alavi (پژوهشهای حقوقی)
Criminal law plays a unique role in protecting environmental rights. Ecocide as an environmental problem is a global problem that has transcended national borders and turned into environmental pollution and regional and global ecosystem problems. The use of criminal law and determining the guarantee of execution, both in the domestic and international dimensions, to protect environmental rights, will have an effective impact on the protection of the global environment. Internationally, environmental rights are defined as the right to have a good environment. However, this concept is developing and a precise definition of the crime of ecocide of material and spiritual elements and what place ecocide has in the definition of the crime has not yet been provided. Governments, groups, and companies with power and wealth, as the main cause of environmental destruction, what restrictions do they create in establishing and passing laws related to ecocide? This article analytically and descriptively shows that criminal behavior in the field of environmental crimes is a very serious issue. These behaviors include illegal activities related to water and air pollution, destruction of natural resources, illegal hunting and wildlife trade, migration developments, smuggling of biological products, and other activities that harm the environment as destruction. In other words, the purpose of this research is to map where ecocide is located under the criminal law offense and provide directions for future research.